Teoria da complexidade e racionalidade ambiental: um estudo bibliométrico acerca dos estudos de Leff e Morin - Priscila Cembranel (Ciências Sociais Unisinos)
This study seeks to elucidate relations between the Complexity Theory, coined by Edgar Morin, and the Environmental Rationality, developed by Enrique Leff, considering publications of other authors within the theme. We tried to identify publications between the periods of 2008-2012 approaching the themes in sociology and management to develop the relationship between the theories of complexity and environmental rationality. We identified four relevant and aligned articles with the Environmental Rationality and 9 aligned with Complexity Theory in a worldwide database. The bibliometric analysis of this portfolio was performed describing qualitatively the results that lead to the development of theoretical frameworks on articles, authors and journals featured about Leff and the environmental rationality and Morin and the Complexity Theory.